(untitled) (ALPHA. Journal of Arts, Literature and Philosophy, 2009)
This article traces the debate on the value of improvement in contemporary democratic theory through a discussion of the controversial interpretations of John Rawls and Stanley Cavell of Schopenhauer as Educator by Friedrich Nietzsche. It argues that the readings of perfectionism offered y both Rawls and Cavell poorly capture the Nietzschean notion of individual freedom as responsibility. The latter may turns out to be of value for modern democratic life not in virtud of, but despite the fact that it constitutes an alternative to the liberal conceptions of culture and individual freedom.